(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
An analytical determination of electric voltage generated by the pressure-driven flow through complex microchannels was analyzed based on the fractal theory. The pressure-driven flow through a complex microchannel with consideration of electrokinetic phenomena is described by the momentum and Poisson- Boltzmann (P-B) equations. The solution of induced electric field strength and electric voltage across complex microchannels are obtained using the fractal theory and technique, which are the function of dimensionless electroosmotic radius and the porosity. The results obtained show that the analytical results are agreed well with the experimental data.